2013
DOI: 10.1155/2013/846126
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Standardized Extract ofGinkgo bilobaagainst Cisplatin-Induced Nephrotoxicity

Abstract: Cisplatin (CDDP) is a potent antitumor compound widely used with a notably side effect of nephrotoxicity inducing oxidative stress and apoptosis in kidneys. Standardized extract from the leaves of the Ginkgo biloba trees, labeled EGb761 (EGb), has been available on the market for its beneficial effects. The purpose of this study was to investigate the ability of EGb to prevent the nephrotoxic effect of CDDP and the mechanisms involved. Our results showed that EGb treatment restored the levels of creatinine, BU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 39 publications
6
29
0
Order By: Relevance
“…Song et al [13] reported the same findings in renal histology after cisplatin treatment. These histopathological findings were ameliorated by Arjunolic acid administration indicating its renopreventive effect against cisplatin-induced nephrotoxicity.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Song et al [13] reported the same findings in renal histology after cisplatin treatment. These histopathological findings were ameliorated by Arjunolic acid administration indicating its renopreventive effect against cisplatin-induced nephrotoxicity.…”
Section: Discussionsupporting
confidence: 55%
“…In this study, Arjunolic acid, a natural product with antioxidant properties, was used for the first time as a renoprotective agent aiming to reduce or reverse cisplatin-induced nephrotoxicity. The experimental design was taken from previous studies that used natural antioxidants as nephroprotective agents in cisplatininduced renal injury [11,13]. The elevation of serum creatinine and BUN was indicated for cisplatin nephrotoxicity as shown in previous studies [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CP triggers ROS generation in the kidney, and these ROS directly act on multiple cell components, including lipids, proteins, and DNA [30]. Interestingly, previous studies have shown that DP showed anti-oxidant activity [18], and our study demonstrated that DP could reverse CP-induced ROS generation in NRK-52E cells.…”
Section: Discussionsupporting
confidence: 53%
“…29 Our experiment showed a significant elevation of renal caspase-3 and bax expressions in CDDP-treated rats in comparison with normal rats which coincides with previous studies. 23,30,31 To our knowledge, this is the first study to examine the effect of candesartan in CDDP-induced nephrotoxicity. Our results demonstrated that both candesartan and BM-MSCs reduced the levels of serum creatinine and urea in CDDPtreated animals.…”
Section: 17mentioning
confidence: 96%